2022
DOI: 10.1093/oncolo/oyac120
|View full text |Cite
|
Sign up to set email alerts
|

KIT-Associated Familial GIST Syndrome: Response to Tyrosine Kinase Inhibitors and Implications for Risk Management

Abstract: Sporadic gastrointestinal stromal tumors (GIST) are rare tumors, with a median age at diagnosis of 60 years. Familial GISTs are very rare and typically associated with earlier onset, with an average age at diagnosis of 48 years. To date, just over 50 familial cases associated with a germline variant KIT or PDGFRa genes have been published. Therefore, there are many challenges in managing these patients, including the timing of starting systemic treatment, considering that most patients have been asymptomatic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The occurrence of GISTs associated with familial syndromes is extremely rare, and most cases present wild-type KIT and platelet-derived growth factor alpha (PDGFRA) [ 13 ]. To date, GISTs with germline KIT pathogenic variants have been described in only 30 families worldwide [ 14 ]. Here, we report the case of a 32-year-old male patient diagnosed in the cancer genomic medicine unit with advanced GISTs throughout the upper stomach and hyperpigmented skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of GISTs associated with familial syndromes is extremely rare, and most cases present wild-type KIT and platelet-derived growth factor alpha (PDGFRA) [ 13 ]. To date, GISTs with germline KIT pathogenic variants have been described in only 30 families worldwide [ 14 ]. Here, we report the case of a 32-year-old male patient diagnosed in the cancer genomic medicine unit with advanced GISTs throughout the upper stomach and hyperpigmented skin.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer gene panel examination simultaneously investigates multiple genes in cells from resected cancer tissue. If pathogenic variants (i.e., druggable variants) are detected, drugs or substances tested in clinical trials/clinical studies potentially effective against the pathogenic variants are selected, including from the cancer genomic database, based on clinical guidelines on chemotherapy [ 14 , 15 ]. In other words, when a cancer genome test detects pathogenic variants of genes in tumor-constituting cells, it is preferable to select antitumor agents that specifically act on the pathogenic variants.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, there has been a great interest in determining the genetic characteristics of these neoplasms, and it was identified and determined that GISTs are characteristically driven by activating mutations of KIT in approximately 85–90% of cases ( 12 14 ). Recent studies have shown that introducing effective tyrosine kinase inhibitors (TKIs), particularly imatinib, have been investigated as potential treatments for GISTs with inoperable or metastatic disease ( 15 , 16 ). In 2002, TKIs was first approved by the FDA for the treatment of patients with metastatic GISTs, which improved median overall survival (OS) from less than 1 year to 5 years ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%